„Over-saturated” constructionist Kenneth Gergen and his offer tendered to (cultural) psychologists - Pankalla, Andrzej; Bakalarz, Krzysztof; Bezdziecki, Robert (Studia Psychologica: Theoria et praxis, 2010)
The text is focused on not-precisely known or at least not widespread and fully accepted among psychologists theory of very well known (and controversial) researcher Kenneth Gergen. It deals with his dialogue with mainstream psychology, his version of social constructionism offered to cultural psychologists and his attitude toward language, narrative and last but not least research method of psychology